LOCAL WISDOM VALUES IN SUPPORTING FOREST CONSERVATION IN SEBANGAU NATIONAL PARK, CENTRAL KALIMANTAN PROVINCE - Manalu, Sanggam R. I. (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
This research aims at identifying the values of local wisdom in the forest conservation, describing the community knowledge on those values and describing the community response in forest conservation. The expected results are: (1) documentations of local wisdom values in the management of Sebangau National Park, (2) community knowledge on the local wisdom values, and (3) community response on the local wisdom values in forest conservation in the Sebangau National Park region. This is a descriptive research to explore values, knowledge, and community response on the local wisdom values in forest conservation in the Sebangau National Park region. Data was gathered by interview, questionnaire, and discussion. The resource persons in this research are community figures, community leaders/DamangKepalaAdat, and anthropologists. Based on the research results, it is concluded that: (1) local wisdom values which support Sebangau National Park conservation include the management of rivers and creeks, management of Jelutung/Pantung trees, Gemor trees management, forest management (natural resources such as fruits, woods, forest vegetables, herbs, etc), lake or deep pools management, river demarcation management; (2) community knowledge on local wisdom values to support Sebangau National Park is spread unevenly. The level of understandings spread between good (22.22%), well (27.78%), bad (11.11%), and even do not understand at all (38.89%); (3) overall the community agree on the local wisdom values to support the conservation of Sebangau National Park.